KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Aryesam, Agnes; Tijow, Meylani Aljeinie; Panda, Florentina Maria (NOKEN : Jurnal Pengelolaan Pendidikan, 2021)
This study aims to describe the managerial competence of principals in improving the professional competence of teachers. The object of research is the principal and teachers in one of the public junior high schools in Jayapura. The approach used is descriptive qualitative which describes explicitly the managerial competence of the principal in improving the professional competence of teachers. Data was collected through observation, interviews and documentation studies which were then analyzed and tested for validity using the triangulation method. The results of the study show that (1) the principal has carried out the planning function together with the teacher, namely preparing annual programs, semester programs, monthly programs, daily programs, and year-end programs. In addition, the principal and the teacher are directly involved in the preparation of the curriculum. (2) The principal carries out the organizing function by dividing tasks to each teacher according to their competences, the preparation of the school organizational structure always involves all competent school components. (3) The principal carries out the actuating function by motivating teachers for career development, ensuring the implementation of all planned school programs. (4) The principal carries out the control function by playing an active role in supervising and evaluating learning program. In addition, the principal supervises the teacher's performance and follows up on it.Keywords: Managerial competence; competences of teachers; Quantitative Research.